Compassionate de-escalation of life-sustaining treatments in pediatric oncology: An opportunity for palliative care and intensive care collaboration - Cuviello, Andrea; Pasli, Melisa; Hurley, Caitlin; Bhatia, Shalini; Anghelescu, Doralina L.; Baker, Justin N. (Frontiers in Oncology, 2022)
Context Approximately 40%-60% of deaths in the pediatric intensive care unit (PICU) are in the context of de-escalation of life-sustaining treatments (LSTs), including compassionate extubation, withdrawal of vasopressors, or other LSTs. Suffering at the end of life (EOL) is often undertreated and underrecognized. Pain and poor quality of life are common concerns amongst parents and providers at a child’s EOL. Integration of palliative care (PC) may decrease suffering and improve symptom management in many clinical situations; however, few studies have described medical management and symptom burden in children with cancer in the pediatric intensive care unit (PICU) undergoing de-escalation of LSTs. Methods A retrospective chart review was completed for deceased pediatric oncology patients who experienced compassionate extubation and/or withdrawal of vasopressor support at EOL in the PICU. Demographics, EOL characteristics, and medication use for symptom management were abstracted. Descriptive analyses were applied. Results Charts of 43 patients treated over a 10-year period were reviewed. Most patients (69.8%) were white males who had undergone hematopoietic stem cell transplantation and experienced compassionate extubation (67.4%) and/or withdrawal of vasopressor support (44.2%). The majority (88.3%) had a physician order for scope of treatment (POST – DNaR) in place an average of 13.9 days before death. PC was consulted for all but one patient; however, in 18.6% of cases, consultations occurred on the day of death. During EOL, many patients received medications to treat or prevent respiratory distress, pain, and agitation/anxiety. Sedative medications were utilized, specifically propofol (14%), dexmedetomidine (12%), or both (44%), often with opioids and benzodiazepines. Conclusions Pediatric oncology patients undergoing de-escalation of LSTs experience symptoms of pain, anxiety, and respiratory distress during EOL. Dexmedetomidine and propofol may help prevent and/or relieve suffering during compassionate de-escalation of LSTs. Further efforts to optimize institutional policies, education, and collaborations between pediatric intensivists and PC teams are needed.